A review on Sperata aor (Hamilton, 1822), a popular food fish of Indian Subcontinent - Sandipan Gupta, (Universiti Kebangsaan Malaysia, 2015)
Sperata aor is a freshwater catfish of Bagridae family which is distributed throughout Indian subcontinent including India, Bangladesh, Pakistan, Nepal and Myanmar. It is a popular food fish due to its good taste and high nutritional value. Recently it has also made its entry in domestic ornamental fish markets of India and has been reported to have moderate export price too. Earlier, few works on different aspects of its morphology and biology have been carried out but no consolidated review is available on these aspects. Therefore, the current work was done to sum up all available information on these aspects to fill the information gap that will be beneficial to its future fishery. Considering all available information, knowledge on food and feeding habit of this fish species is satisfactory, except detail information on spatial variation of its breeding periodicity, proper information on other aspects are still lacking. No work has been conducted to examine its captive culture potential or for induced breeding. Further work should be done to explore its future fishery.